Etika Berinteraksi Dengan Penyandang Disabilitas di Lingkungan Masyarakat Kota Lhokseumawe - Ery Wati; Zulkifli (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2026)
As members of society, we all have a role to play in creating an inclusive and welcoming environment for everyone, including people with disabilities. Ethical interactions with people with disabilities are not just about being polite, but also about understanding, respecting, and supporting their rights as equal individuals. However, often misunderstandings in unethical communication can cause people with disabilities to feel marginalized, lack confidence, and not participate in community activities. For example, neighbors or colleagues often use derogatory language, do not give people with disabilities enough time to respond, or do not use appropriate communication aids. This has a negative impact on the social-emotional development of people with disabilities. The method of implementing this Community Service activity lasts 3 (three) days, namely 7 and 8 in a room with 10 participants with disabilities with different obstacles, while on the 9th the participants and the service team went down to the field consisting of 4 (four) villages divided into groups. The results achieved in this community service activity are that participants with disabilities understand the concept of disability, obstacles and can practice ethics in interacting with other disabilities. Meanwhile, the results obtained in the Community are being able to understand disabilities, obstacles and being able to interact with people with disabilities even though there are only a few simulation examples.